2014
DOI: 10.1017/s1461145714000212
|View full text |Cite
|
Sign up to set email alerts
|

Acute but not sustained aromatase inhibition displays antidepressant properties

Abstract: Aromatase inhibitors block the conversion of androgens to oestrogens and are used for the treatment of hormone-responsive breast cancer in menopause and recently also in premenopausal women. We investigate whether decreased oestrogen synthesis following aromatase inhibition leads to a depressive-like behavioural response in cycling female rats. Using the forced swim test (FST) we estimate the response of acute (three injections in 24 h) and sustained (7 d) letrozole and fluoxetine administration. Acute aromata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 26 publications
4
17
0
Order By: Relevance
“…Another non-steroidal aromatase inhibitor, letrozole, was used in experiments with gonadally intact rats. The dose of letrozole (1 mg/kg) was chosen based on a previous study of affective behavior in rats ( Kokras et al, 2014 ), as well as a pharmacokinetic study of letrozole-cyclodextrin complex ( Wempe et al, 2007 ).…”
Section: Methodsmentioning
confidence: 99%
“…Another non-steroidal aromatase inhibitor, letrozole, was used in experiments with gonadally intact rats. The dose of letrozole (1 mg/kg) was chosen based on a previous study of affective behavior in rats ( Kokras et al, 2014 ), as well as a pharmacokinetic study of letrozole-cyclodextrin complex ( Wempe et al, 2007 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, the precise mechanisms of depression‐associated deficits and how oestrogens impact on these remains unclear and requires further investigation. Finally, although we have focussed on 17β‐oestradiol, other hormones, in particular testosterone and progesterone, have been implicated in depressive‐like behaviours in rodents and warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the effects of letrozole on cognition have attracted more attention, but the evidence for its effects on depression is less understood. Both clinical and pre-clinical trials have found opposing effects of letrozole on mood and behavior (Borbélyová et al, 2017;Chang et al, 2015;Kokras et al, 2018Kokras et al, , 2014Meng et al, 2011). Most animal studies to date have used rodents of varying ages, gonadal hormone status, sex, and duration of treatment, resulting in conflicting data that are poorly understood.…”
Section: Introductionmentioning
confidence: 99%